Structural Behavior of Masonry Panels Strengthened with Textile-Reinforced Mortar - Ungureanu, Dragos; Taranu, Nicolae; Ghiga, Dan Alexandru; Isopescu, Dorina Nicolina; Mihai, Petru; Cozmanciuc, Ruxandra (Technological Innovation in Engineering Research Vol. 7, 2022)
This book chapter presents the results of an experimental and numerical program carried out on unreinforced masonry panels strengthened by textile-reinforced mortar (TRM) plastering. Unreinforced masonry is one of the common types of structure in the world especially in seismically active regions such as South and East of Europe, South America, Middle East and New Zealand. Past earthquakes have revealed the imperativeness necessity for seismic rehabilitation of these structures. In order to determine the effectiveness of the TRM plastering method, five panels were constructed, instrumented and tested in diagonal shear mode. As a reference, two panels were examined. While the second reference panel was fortified using a conventional self-supporting cement mortar matrix reinforced with steel meshes, the first reference panel was left unenhanced. The remaining three panels were joined using transversal composite anchors and fortified with TRM plastering that was applied to one or both faces. The numerical and experimental findings demonstrated the TRM systems' good effectiveness, particularly when used on both panel facings.